Prenatal Diagnosis and Management of a Rare Central Tendon Defect Type of Congenital Diaphragmatic Hernia with a Massive Pericardial Effusion. (22nd January 2020) - Babic, Inas; Al-Jobair, Haifa; Al Towaijri, Osama; Al-Shammary, Huda; Atiyah, Merna; Al Hudhaif, Jamal; Ammari, Amer
Abstract : The central tendon defect type of congenital diaphragmatic hernia (CDH) is extremely rare and usually associated with a significant pericardial effusion. Prenatal diagnostic ultrasound features of this quite rare entity remain often overlooked or misdiagnosed. There is a dearth of literature about the role of prenatal intervention, often through an elective pericardiocentesis, for the prevention of lung hypoplasia and to decrease the overall neonatal morbidity and mortality. To the best of our knowledge, till date, there is only one case that was subjected to a prenatal intervention. Here, we present a second case of a central tendon defect type of CDH with a large pericardial effusion that was subjected to a prenatal transthoracic pericardiocentesis. Although smooth intubation and ventilation were performed immediately after birth, the infant suffered for several months from respiratory instability. Laparoscopic central tendon hernia repair was performed, and neonate was discharged home at seven months of age. Although prenatal pericardiocentesis may facilitate smoother postnatal intubation and ventilation, its broader effect on respiratory function is uncertain and still remains elusive.